1998
DOI: 10.1038/sj.onc.1202199
|View full text |Cite
|
Sign up to set email alerts
|

Design and properties of a Myc derivative that efficiently homodimerizes

Abstract: bHLH and bHLHZip are highly conserved structural domains mediating DNA binding and speci®c proteinprotein interactions. They are present in a family of transcription factors, acting as dimers, and their selective dimerization is utilized to switch on and o cell proliferation, dierentiation or apoptosis. Myc is a bHLHZip protein involved in growth control and cancer, which operates in a network with the structurally related proteins Max, Mad and Mnt. It does not form homodimers, working as a heterodimer with Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
182
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(192 citation statements)
references
References 45 publications
8
182
2
Order By: Relevance
“…Omomyc DNA, carrying an ATG start codon, 7,8 was amplified from the pBPOmomyc construct by PCR primed using oligonucleotides containing the NotI restriction site. The resulting Omomyc sequence was fused to the Involucrin promoter, into the NotI site of the Involucrin expression cassette.…”
Section: Transgene Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omomyc DNA, carrying an ATG start codon, 7,8 was amplified from the pBPOmomyc construct by PCR primed using oligonucleotides containing the NotI restriction site. The resulting Omomyc sequence was fused to the Involucrin promoter, into the NotI site of the Involucrin expression cassette.…”
Section: Transgene Constructionmentioning
confidence: 99%
“…Overexpressed Omomyc competes with Max for Myc and thereby prevents Myc from binding to the E-box and activating transcription. 7 In contrast, Myc-dependent trans-repression, which does not involve binding to the E-box, is unaffected, or even enhanced, by Omomyc. 8 The strong proapoptotic activity of Omomyc mutant protein may spring from its ability to differentially influence activated and repressed Myc transcriptional targets.…”
Section: Introductionmentioning
confidence: 99%
“…The link between Myc gene regulation and transformation has been explored using various altered forms of Myc, and studies have demonstrated that Myc/Max heterodimerization is critical for transactivation, transrepression, and transformation (Amati et al, 1993a;Desbarats et al, 1996;Facchini et al, 1997;Soucek et al, 1998). For example, MycEG and MaxEG, c-Myc and Max proteins with modi®ed leucine zipper domains that can heterodimerize with each other but not with endogenous proteins, must be expressed together to transform cells and to transactivate gene expression from a Myc/Max DNA binding site (Amati et al, 1993a).…”
Section: Cellular Transformation By Mycmentioning
confidence: 99%
“…OmoMYC comprises the carboxy-terminal basic region, helix-loop-helix and leucine zipper of MYC and carries four point mutations in the leucine zipper that are intended to alter its dimerization properties 20 . Here, we present an analysis of the OmoMYC structure, its genome-wide chromatin binding and gene regulation to understand its astounding ability to discriminate physiological from oncogenic functions of MYC.…”
Section: Introductionmentioning
confidence: 99%